Telomere Length Reprogramming in Embryos and Stem Cells. (27th February 2014) - Kalmbach, Keri; Robinson, LeRoy G.; Wang, Fang; Liu, Lin; Keefe, David
Abstract : Telomeres protect and cap linear chromosome ends, yet these genomic buffers erode over an organism's lifespan. Short telomeres have been associated with many age-related conditions in humans, and genetic mutations resulting in short telomeres in humans manifest as syndromes of precocious aging. In women, telomere length limits a fertilized egg's capacity to develop into a healthy embryo. Thus, telomere length must be reset with each subsequent generation. Although telomerase is purportedly responsible for restoring telomere DNA, recent studies have elucidated the role of alternative telomeres lengthening mechanisms in the reprogramming of early embryos and stem cells, which we review here.